Glaciological studies of the Institute of Geography, RAS, on the Elbrus Mount in 2017 - V. N. Mikhalenko; S. S. Kutuzov; I. I. Lavrantiev; P. A. Toropov; A. A. Аbramov; A. A. Polyukhov (Лëд и снег, 2017)
.